The Effect of Vacuum Impregnation Pretreatment on Air-Drying Kinetics of Pears - Şeyma Uysal; Fikret Pazır (Turkish Journal of Agriculture: Food Science and Technology, 2020)
The aim of this study was to examine the drying kinetics of pears (Pyrus communis L.) with and without vacuum impregnation and under the different temperature by using tray dryer. Vacuum impregnation were applied to the the pears (15 mm thickness, 65 mm outer and 20 mm inner dimensions respectively) with the conditions of 50⁰ Brix impregnation solution concentration, 225 mbar vacuum pressure and 45 min vacuum time. Drying process was carried out at temperatures of 55, 65 and 75°C. Drying time of non-vacuum impregnated pears was determined 640, 500 and 340 min and vacuum impregnated pears was determined 700, 540 and 560 min respectively. Page, Exponential, Henderson and Pabis, Diffusion Approach were examined for testing the drying kinetics. Experimental values are in accordance with the expected values resulted Page and Difussion models of with and without vacuum impregnated pears. Effective diffusion coefficient (Deff) was varying 2.74×10-11 to 7.31×10-11 m2/s. m2/s with respect to the drying temperatures. The activation energy for the non-vacuum impregnated and vacuum impregnated pears was 32.93 kJ / mol and 24.25 kJ / mol, respectively.